Sleep Reactivity and Depressive Symptoms Among Chinese Female Student Nurses: A Longitudinal Mediation Analysis - Shi, Xuliang; Qi, Haiying; Wang, Shuo; Li, Zihan; Li, Zhipeng; Fan, Fang (Frontiers in Psychiatry, 2021)
Previous cross-sectional studies have documented that sleep reactivity was associated with depressive symptoms, but the potential mechanisms underlying this relationship were understudied. Therefore, the present study with a longitudinal prospective design was to reveal the mediating roles of sleep disturbance and emotion regulation difficulties (ERD) between sleep reactivity and depressive symptoms. This study included 725 student nurses who were followed up periodically for 9 months, with an interval of three months. All participants completed questionnaires regarding sleep reactivity, sleep disturbance, ERD, and depressive symptoms. Adjusted analyses suggested that the direct effect of sleep reactivity on depressive symptoms was non-significant. The bootstrap procedure revealed two significant indirect effects: from sleep reactivity to depressive symptoms with sleep disturbance as a mediator and from sleep reactivity to depressive symptoms with sleep disturbance and ERD as sequential mediators. Therefore, sleep reactivity might be considered as an indicator of shiftwork adaptability in the evaluation of recruitment. Psychological interventions aimed at developing healthy sleep habits and emotion regulation skills may be helpful in decreasing the risk of depression.